STRATEGI INOVASI PRODUK PERBANKAN SYARIAH DALAM MENINGKATKAN JUMLAH NASABAH DI PT. BPRS DAYA ARTHA MENTARI BANGIL PASURUAN - Anik Fatimatuzahro; Aslikhah Aslikhah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2019)
PT. BPRS Daya Artha Mentari Bangil Pasuruan was the first BPRS established in the Pasuruan regency. Over time many other Islamic banks were newly established so that PT. BPRS Daya Artha Mentari Bangil Pasuruan has many competitors. So that PT. BPRS Daya Artha Mentari Bangil Pasuruan must have strategies to increase the number of its customers.The problem examined in this study is how literacy of sharia banking product innovation and how is the innovation strategy of shariah banking products in increasing the number of customers. This study aims to determine customer literacy about sharia banking product innovation and also to find out sharia banking product innovation strategies in increasing the number of customers. The method used in this research is descriptive qualitative research method. This research uses observation, documentation, and interview data collection techniques. The results of this study concluded that customer literacy about product innovation at PT. BPRS Daya Artha Mentari Bangil Pasuruan is still low. And product innovation strategies in increasing the number of customers are done by looking at the needs of the community, BPRS still exist to offer product in the midst of competition, and to socialize each new product and all components of the bank to synergize well and compactly